DEVELOPMENT OF MATHEMATICS LEARNING INSTRUMENTS OF PROBLEM BASED LEARNING MODEL ON SETS MATERIAL FOR THE 7TH GRADE OF JUNIOR HIGH SCHOOL - Meilinda Erika; Titi Solfitri; Zulkarnain (Jurnal Prinsip Pendidikan Matematika, 2021)
This research is motivated by the limited mathematics learning devices that are in accordance with the 2013 Curriculum. This research purposed is to produce mathematics learning devices such as syllabus, lesson plans, and student worksheets by using problem based learning on sets material for the seventh grade of junior high school. The development model used in this research is the 4-D model which consists of the stages of define, design, develop, and disseminate. The learning devices that have been developed were validated by three validators and revised according to suggestions from the validators. The average score of the validation results for the syllabus, lesson plans, and student worksheets are 90.25%, 91.25%, and 91.75% with very valid categories. The results of this validation indicate that the syllabus, lesson plans, and student worksheets are feasible to be tested. Researcher conducted trials one by one on six students to see the students responses and readability to student worksheets developed with a problem based learning model. It was found that the student worksheets being developed can help them in studying the set material, is easy to understand, the explanation is clear enough and the students worksheets looks interesting. Based on the results of data analysis and discussion it can be concluded that the syllabus, lesson plans, and student worksheets by using problem based learning model on sets material for the seventh grade of junior high school has fulfilled valid.